Law and morality in Malaysia: an overview of selected issues relating to transsexuals, prostitution and organ transplant / Nasuhah Mohamed Ali and Muna Farhana Halim - Mohamed Ali, Nasuhah; Halim, Muna Farhana (2008)
This research paper is primarily concerned with law and morality in Malaysia. It gives an overview on selected issues relating to transsexuals, prostitution and organ transplants. We will discuss on the different forms of morality in respect of the matters mentioned herein. The position from the Islamic perspective on the different issues is discussed and at the same time, it is compared with the ever changing public attitude on the issues on the acceptable standards of public morality. Therefore, this research paper will discuss specifically on laws and morals relating to transsexuals, prostitution and organ transplant and to show its relationship with the question of morality and the effect of the standards of law and morality on the subject matter. At the end of this research, we will be able to see a different perspective in the law and the influence of the morality on the law and its relationship with society as a whole.